Implementasi Problem Based Learning (PBL) pada Mata Pelajaran Matematika - Radhiya Rasyada (BASICA, 2023)
Mathematics is often considered difficult and confusing for students. The purpose of writing this work is to determine the implementation of Problem Based Learning (PBL) in Mathematics Class 5 MIN 4 Ponorogo. In research regarding the implementation of PBL in Mathematics Class 5 MIN 4 Ponorogo, descriptive qualitative methods were used through observation, interviews with teachers, and documentation. Data analysis was carried out using a thematic approach developed by Huberman and Miles to understand how PBL was implemented and its impact on students' understanding and skills. The results of this work are a) Implementation of Problem-Based Learning (PBL) at MIN 4 Ponorogo increases students' active participation and collaboration skills, supported by the use of technology, and increases their problem-solving abilities and motivation. b) Implementation of Problem-Based Learning (PBL) at MIN 4 Ponorogo faces technological obstacles, including computer facilities, lack of smart TV, and unstable internet access. Solutions include technology improvements, use of AV equipment, network infrastructure improvements, collaboration with internet service providers, and teacher training.